Dual Polarity Ion Confinement and Mobility Separations - Attah, Isaac K. (J Am Soc Mass Spectrom, 2019)
Here we present simulations and describe the initial implementation of a device capable of performing simultaneous ion mobility (IM) separations of positive and negative ions based upon the structures for lossless ion manipulations (SLIM). To achieve dual polarity ion confinement, the DC fields used for lateral confinement in previous SLIM were replaced with RF fields. Concurrent ion transport and mobility separation in the SLIM device are shown possible due to the nature of the traveling wave (TW) voltage profile which has potential minima at opposite sides of the wave for each ion polarity. We explored the potential for performing simultaneous IM separations of cations and anions over the same SLIM path and the impacts on the achievable IM resolution and resolving power. Initial results suggest comparable IM performance with previous single-polarity SLIM separations can be achieved. We also used ion trajectory simulations to investigate the capability to manipulate the spatial distributions of ion populations based on their polarities by biasing the RF fields and TW potentials on each SLIM surface so as to limit the interactions between opposite polarity ions.